EKSISTENSI ADAT, TANAH ULAYAT DAN PARIWISATA DI KASEPUHAN CIPTAGELAR, JAWA BARAT - Tri Suyud Nusanto; Nur Widiyanto (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
The article aimed at understanding the dynamics within the encounter between Islam and tatali paranti karuhun, the local religion as the central source of spirituality and cultural practices of Kasepuhan Ciptagelar living on the Halimun Salak National park, West Java. The tradition is rooted in Pre-Islamic Sundanese culture that is often placed as the part of Sunda Wiwitan belief, which is, as the other local beliefs in Indonesia, not being recognized as the official religion. On the other hand, although have been inhabiting the area forhundred years the establishment of national park have placed the people as the illegal settler within the state’s forest. Thus, there are two pressures for the people; the freedom to practice their local tradition rooted in a local belief which is different from the majority group and the limited legal access toward their customary land. Fortunately, Kasepuhan Ciptagelar is blessed by various tourism resources, both in the term of eco-tourism and cultural tourism rooted in the authenticity of Sundanese culture. In this case, the study offers new insight that the arrival of tourism has given the opportunity for the people to strengthen their cultural identity and the legal access toward the customary land. The ethnographic research through participant observation to gather the primary data reveals that tourism has effectively mediated the encounter between Islam, local belief and the struggle to re-claim the customary land.